Image transmission over LoRa for mangrove monitoring - Jebril, Akram Hussein A. (2019)
LoRa as a Low Power Wide Area Network (LPWAN) is considered as one of the future wireless communication standard for IoT Internet of Things (IoT), this because it offers features such as; long range, low cost, less power consumption which make it an optimum alternative to the current wireless networks such as; ZigBee, Wi-Fi, Bluetooth-LE, IEEE 802.15.4, Sigfox and traditional cellular technologies. LoRa can replace the current technologies and communication systems used to monitor mangrove forests in Malaysia, where it covers a 2% of the total land area. It also provides a protection for the beaches and coastlines from storms, waves, floods, and soil erosion. However, LoRa has a limited bandwidth which makes it difficult to transfer data from image sensors in mangrove forests. This thesis has a significant contribution in proving the concept of using LoRa for the first time worldwide as the wireless sensor network to monitor mangrove forests; and overcome the problem of transferring images over LoRa limited bandwidth by proposing a novel image transmission scheme. This novel scheme converts images with resolution of 160x120 pixels taken for mangrove forests to hexadecimal format in form of packets then transfer these packets over LoRa physical layer. Indoor and outdoor tests were conducted before visiting the mangrove forests to find the optimum LoRa sittings of Spreading Factor (SF), Coding Rate (CR) and preamble numbers. In addition, the measurements of Packet Loss Rate, Peak Signal to Noise Ratio (PSNR) and Structural Similarity Index Measure (SSIM) for each transferred image over LoRa were conducted to evaluate the transferred images over LoRa physical layer using the novel scheme. The positive outcome of images transmission over LoRa physical layer was used for the first time up to 7km with PSNR values between 30dB and 70 dB which indicate to higher quality of the received images,also, the project does not need to additional costs such as; building complicated infrastructures or even buying repeaters. This research proves the concept of point- to-point communication by transmitting image data over the LoRa physical layer despite its limitation in data transmission. In addition, the possibility of using LoRa as a preferred technology in terms of the long range, low cost, and lower power consumption for mangroves monitoring in Malaysian.